Profiling coaching training: what is a suitable coaching training curricula? - Farinha, Carolina Gomes (2017)
This study aims to shed some light into the debate of what is a suitable coaching training curricula, specifically in Portugal. We conducted a Delphi study with 5 coaching experts to analyse: i) what is the minimum academic training for a future coach, ii) what is the minimum of hours required for a coaching training program, iii) which competencies should it develop, iv) which contents should the training address, v) which are the requisites for one to be a coaching trainer and, vi) what mechanism should regulate coaching practice. The results show a consensus regarding the coaching competencies profile, which are both the standard of coaching competencies in market. Minimum education background (university degree) also achieved consensus which is superior to market requirements. We also achieved consensus for the requisites to be a coaching trainer but the standards are partially in accordance with the market information. The minimum of hours did not achieve consensus and the minimum of hours required in the study are superior to many coaching programs available. Coaching training contents did not achieve consensus. For coaching practice regulation, the International Coach Federation (ICF) seems to be the preferred regulator entity. Key-words: .